NOP Receptor Ligands as Potential Agents for Inflammatory and Autoimmune Diseases. (17th November 2011) - Gavioli, Elaine C.; Romão, Pedro R. T.
Abstract : Nociceptin/orphanin FQ (N/OFQ) is a seventeen-amino acid peptide that is the endogenous ligand of a G-protein-coupled receptor (NOP). Various immune cells express the precursor protein and secrete N/OFQ as well as display binding sites for this peptide. The functional capacity of NOP receptor was demonstrated in vitro and in vivo studies by the ability of N/OFQ to induce chemotaxis of immune cells, to regulate the expression of cytokines and other inflammatory mediators, and to control cellular and humoral immunity. In this context, N/OFQ could modulate the outcome of some inflammatory diseases, such as sepsis and autoimmune pathologies by mechanisms not clearly elucidated yet. In fact, human body fluid revealed increased levels of N/OFQ under sepsis, arthritis, and Parkinson's diagnose. Preclinical studies pointed to the blockade of NOP receptor signaling as successful in treating these experimental conditions. Further preclinical and clinical studies are required to investigate the potential of NOP ligands in treating inflammatory diseases.